The Politics of Tradition : Continuity and Change in Northern Nigeria, 1946-1966 - Whitaker, C. S. (C. Sylvester), 1935-2008 (Book collections on Project MUSE., 1970)
Taking Northern Nigeria during the years 1946 to 1966 as an example, Professor Whitaker shows how modern institutions-parliamentary representation, a cabinet system, popular suffrage, and political parties-were introduced and how they resulted not in a displacement of tradition but in an astute absorption by traditional forces. Originally published in 1970. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original t.